Implementation of Acrostic Technique in Poetry Writing Skills of Indonesian Language Subject for Students in VIII B Class at SMP Negeri 11 Bengkulu Tengah - Reifika Koumala Sari; Riswanto; Vebbi Andra (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to evaluate the implementation of the acrostic technique in improving poetry writing students' skills in class VIII B at SMP Negeri 11 Bengkulu Tengah. The choice of acrostic technique as a learning method is to help students understand and apply the intrinsic elements and structure of poetry’s in a more creative and structured manner. This research uses a qualitative approach that uses observation, interview, and documentation methods. This study involved 27 students as research subjects. The results showed that using acrostic techniques significantly improved students' ability to compose poetry, in terms of creativity, understanding of poetry structure, and language expression.